2020
DOI: 10.21203/rs.3.rs-42529/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The DDX39B/FUT3/TGFβR-I Axis Promotes Tumor Metastasis and EMT in Colorectal Cancer

Abstract: Background: DDX39B is a member of the DEAD box (DDX) RNA helicase family required for nearly all cellular RNA metabolism processes. The exact role and potential molecular mechanism of DDX39B in the progression of human colorectal cancer (CRC) remain to be investigated. Methods: Western blotting and quantitative real-time PCR (qRT-PCR) were conducted to detect the expression of DDX39B in CRC tissues and cell lines. Transwell and wound healing assays were conducted to assess the migration and invasion ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…38 It is a complicated pathological process that involves multiple steps, including epithelial to mesenchymal transition, in which cancer cells transit between epithelial and mesenchymal states that facilitating cell dissemination. 39 Our results demonstrated that FUT7 siRNA inhibited the migration, invasion, and EMT of bladder cancer cells, while FUT7 cDNA promoted these cell behaviors ( Figures 2 and 3 ). Overall, our study provided novel and valuable insights into FUT7 as a diagnostic biomarker, prognosis predictor, and therapeutic target for BLCA.…”
Section: Discussionmentioning
confidence: 57%
“…38 It is a complicated pathological process that involves multiple steps, including epithelial to mesenchymal transition, in which cancer cells transit between epithelial and mesenchymal states that facilitating cell dissemination. 39 Our results demonstrated that FUT7 siRNA inhibited the migration, invasion, and EMT of bladder cancer cells, while FUT7 cDNA promoted these cell behaviors ( Figures 2 and 3 ). Overall, our study provided novel and valuable insights into FUT7 as a diagnostic biomarker, prognosis predictor, and therapeutic target for BLCA.…”
Section: Discussionmentioning
confidence: 57%